Abu Rabi`, Ibrahim. “Globalization: Is there a Contemporary Islamic Response?” Year 5, Issue 21 (Summer 1421 AH/ 2000 CE), Pp. 9-44. - أبو ربيع إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2000)
Ibrahim Abu Rabi’s article offers observations on globalization, listing three prefaces on reinterpreting the principles of Islam, the social and economic changes in the West, and the education systems in the Muslim world. It discusses the New World Order, the challenge globalization poses to nation-states, and the challenges facing the Muslim mind. It discusses, moreover, the cultural autonomy in the context of globalization and brain drain. And it addresses Zionism and its relationship to globalization. Lastly, it discusses Muslim community life in the United States and questions how an intellectual American-Muslim echelon may be formed, and how it can formulate Islamic answers to the problems created by globalizations and its allies in the Muslim world.